Assessment of the menopausal symptoms of women by using the menopausal rating scale - Pradhan, Shweta; Dave, Anupama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Although menopause is a universal phenomenon, there is a considerable variation among women regarding the manifestation of menopausal signs and symptoms. Symptoms experienced with the menopausal transition and early post menopause are varied and span both physical and psychological domains. Therefore, a need is felt to evaluate menopausal symptoms on a pretested scale to provide a subjective and clinically reproducible picture of menopausal symptoms. Methods: A descriptive cross-sectional study was conducted in MYH ,Indore Obstetrics and Gynecology Department, from July 2016 to December 2016.A pretested, semi structured, interview based, oral questionnaire was used to assess the menopausal symptoms and their severity in women of age group 35 to 65 years attending MYH, Indore OPD, using MRS scale and to evaluate these symptoms in perimenopausal as compared to postmenopausal women. Results: The results were evaluated for psychological (P), somatic (S), and urogenital (U) symptoms. A significantly higher percentage of perimenopausal women showed a P score of ≥7; while a higher percentage of postmenopausal showed S score and U score ≥7 ;p ≤ (0.001).Working women seem to suffer more from psychological symptoms whereas nonworking women showed a greater incidence of somatic symptoms. Conclusions: The present study revealed that proportion of menopausal symptoms was significantly high and there was variation of severity of menopausal symptoms with any of the socio demographic variables, menopausal status or duration of menopause.